Penerapan Sistem Informasi Manajemen Kinerja (SiManja) pada Bidang Penyimpanan, Pengolahan, dan Pelestarian Bahan Perpustakaan di Dinas Perpustakaan dan Arsip Aceh - Aini, Zahriatul; Nailaturrahmi; Rahman, Abdul; Jannah, Syarifah Raihannatul (Jurnal EMT KITA, 2025)
This study aims to examine the implementation of SiManja in the field of storage, processing, and preservation of library materials at the Aceh Library and Archives Service. The research method used is descriptive qualitative, with data obtained through interviews with 10 employees, field observations, and internal document analysis. The results of the study indicate that the implementation of SiManja helps improve employee discipline by filling in Employee Performance Targets (SKP) more systematically and organized. However, some technical obstacles such as difficulty understanding the application are still found. With continuous training and simpler guidance, the effectiveness of the system can be further improved.